2021
DOI: 10.1186/s13058-021-01442-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative fluorescence imaging with aminolevulinic acid detects grossly occult breast cancer: a phase II randomized controlled trial

Abstract: Background Re-excision due to positive margins following breast-conserving surgery (BCS) negatively affects patient outcomes and healthcare costs. The inability to visualize margin involvement is a significant challenge in BCS. 5-Aminolevulinic acid hydrochloride (5-ALA HCl), a non-fluorescent oral prodrug, causes intracellular accumulation of fluorescent porphyrins in cancer cells. This single-center Phase II randomized controlled trial evaluated the safety, feasibility, and diagnostic accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 97 publications
0
38
0
Order By: Relevance
“…One potential caveat is that ALA‐PpIX fluorescence is susceptible to false positives due to inflammation, and it also remains to be seen if ALA‐PpIX can reliably detect DCIS. A recent Phase II randomized control trial [87] using 15 mg/kg oral ALA demonstrated positive predictive values of 100 and 55.6% inside and outside the gross tumor margin, respectively, the latter suggesting a potential impact on reducing re‐excision rates if confirmed in Phase III trials that are in progress. As in other applications, the use of an exogenous fluorescent agent adds cost and regulatory and operational complexities.…”
Section: Specific Optical Approaches For Different Surgical Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential caveat is that ALA‐PpIX fluorescence is susceptible to false positives due to inflammation, and it also remains to be seen if ALA‐PpIX can reliably detect DCIS. A recent Phase II randomized control trial [87] using 15 mg/kg oral ALA demonstrated positive predictive values of 100 and 55.6% inside and outside the gross tumor margin, respectively, the latter suggesting a potential impact on reducing re‐excision rates if confirmed in Phase III trials that are in progress. As in other applications, the use of an exogenous fluorescent agent adds cost and regulatory and operational complexities.…”
Section: Specific Optical Approaches For Different Surgical Needsmentioning
confidence: 99%
“…Ex vivo lumpectomy guidance techniques under development for rapid margin assessment: (A) large‐area OCT showing a commercial prototype system, top view of a lumpectomy specimen held by vacuum bag on the scanner platform, and example image of DCIS (arrow) with corresponding H&E stained histology section (courtesy Dr A. Berkeley, Perimeter Medical) [84]; (B) ALA‐PpIX fluorescence imaging using a hand‐held device (Courtesy Dr R. DaCosta, Princess Margaret Cancer Centre) with a “butterflied” lumpectomy specimen showing a region of DCIS with positive red ALA‐PpIX fluorescence and corresponding histology section indicating close (adapted from Ottolino‐Perry et al [87], with permission); (C) low‐frequency photoacoustic tomography showing a prototype scanner with water‐bath for acoustic coupling to the sample (held in a vacuum plastic bag) and arc‐scanning fiberoptic probe and close‐up of a 930 nm photoacoustic image of a lumpectomy specimen (arrow: positive margin) together with corresponding radiographs and ultrasound images (Courtesy Dr I. Kosik, Western University)…”
Section: Specific Optical Approaches For Different Surgical Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Conversely, fluorescent cellular marking of malignant breast tissue has been demonstrated through pre-operative administration of 5-aminolevulinic acid hydrochloride, but non-malignant proliferative cellular changes in tissue, including hyperplasia, columnar cell change, and atypical ductal hyperplasia, were also shown to give rise to a false-positive fluorescence signal. 16 The combination of multiple modalities provides a potential mitigation to the limitations of each individual imaging technique. In particular, the combination of OCT + fluorescence offers the OCT imaging resolution for visualizing microarchitectural changes associated with many forms of malignancy, 17 detection of critical structures such as blood vessels, 9 and highly specific fluorescence detection of certain forms of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the combination of OCT + fluorescence offers the OCT imaging resolution for visualizing microarchitectural changes associated with many forms of malignancy, 17 detection of critical structures such as blood vessels, 9 and highly specific fluorescence detection of certain forms of cancer. 16 Miniaturized fiber-optic probes that can augment OCT with fluorescence to perform multimodal imaging have been demonstrated in both intravascular [18][19][20] and endoscopic 21 applications. Recent work established the feasibility of inserting a multimodal fiber-optic probe through a guide needle, using both imaging modalities to improve yield in lung biopsies.…”
Section: Introductionmentioning
confidence: 99%